2013
DOI: 10.1039/c3nr00421j
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-enhanced luminescence of silicon quantum dots co-encapsulated in polymer nanoparticles

Abstract: The preparation of two-component polymer composite nanoparticles encapsulating both Si quantum dots (SiQDs) and Au nanoparticles (AuNPs) by a single step miniemulsion polymerization of divinylbenzene is described. This simple and robust method affords well-defined polymer composite nanoparticles with mean diameters in a range of 100-200 nm and with narrow polydispersity indices as determined by dynamic light scattering and transmission electron microscopy. The successful encapsulation of AuNPs within poly(divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 80 publications
5
33
0
Order By: Relevance
“…Previous studies demonstrated that aggregation of AuNPs leads to ar edshift in the plasmon absorption, because of electronic coupling interactions between the neighboring particles. [21,52,53] In harmony to this, we found in the present work that the absorption bands of the core-shell hybrid particles with different weight ratios of TEOS/Au,t hat is, different shell thicknesses, were always approximately 540 nm. Relative to the absorption of AuNPs in aqueous solution, aredshift of 11 nm to longer wavelengths is detected, because of segregation of the nanoparticles at the surface of the PS colloids.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies demonstrated that aggregation of AuNPs leads to ar edshift in the plasmon absorption, because of electronic coupling interactions between the neighboring particles. [21,52,53] In harmony to this, we found in the present work that the absorption bands of the core-shell hybrid particles with different weight ratios of TEOS/Au,t hat is, different shell thicknesses, were always approximately 540 nm. Relative to the absorption of AuNPs in aqueous solution, aredshift of 11 nm to longer wavelengths is detected, because of segregation of the nanoparticles at the surface of the PS colloids.…”
Section: Resultssupporting
confidence: 84%
“…However, according to previouss tudies,t he position of the band is not sensitivet ot he thickness of the silica shell. [21,52,53] In harmony to this, we found in the present work that the absorption bands of the core-shell hybrid particles with different weight ratios of TEOS/Au,t hat is, different shell thicknesses, were always approximately 540 nm. DLS was additionally used to monitorc hanges in the size of the particles.…”
Section: Resultssupporting
confidence: 80%
“…Several approaches to obtain high photoluminescence (PL) extraction with lower QD concentrations have been reported, including surface patterning, [ 32 ] and alternate assembly and the addition of inorganic particles. [ 33 ] Patterning at the interface of films and alternate assembly can be exploited to easily tune fluorescence and obtain strong light emission. [ 34–36 ] However, the complicated process of patterning and assembly has impeded commercialization and fabrication on a large area scale.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity goes up by DNA hybridization ((iv) in Figure 4 (I)). The PL enhancement is considered to be due to the coupling with surface plasmons in Au-NPs [43][44][45][46] , although more detailed analyses including theoretical modelling is necessary for detailed understanding of the enhancement mechanism. On the right side of Figure 4 (I), the PL intensities of several control samples are shown, i.e., mixture of (v) ssDNA conjugated Si-QDs and citrate-stabilized Au-NPs, (vi) untreated Si-QDs and ssDNA, (vii) untreated Si-QDs, ssDNA and citratestabilized Au-NPs and (viii) untreated Si-QDs, ssDNA and DNA functionalized Au-NPs.…”
mentioning
confidence: 99%